Obesity prevalence in Mexico: impact on health and economic burden. Issue 1 (1st February 2013) - Rtveladze, Ketevan; Marsh, Tim; Barquera, Simon; Sanchez Romero, Luz Maria; Levy, David; Melendez, Guillermo; Webber, Laura; Kilpi, Fanny; McPherson, Klim; Brown, Martin
Abstract: Objective: Along with other countries having high and low-to-middle income, Mexico has experienced a substantial change in obesity rates. This rapid growth in obesity prevalence has led to high rates of obesity-related diseases and associated health-care costs. Design: Micro-simulation is used to project future BMI trends. Additionally thirteen BMI-related diseases and health-care costs are estimated. The results are simulated for three hypothetical scenarios: no BMI reduction and BMI reductions of 1 % and 5 % across the population. Setting: Mexican Health and Nutrition Surveys 1999 and 2000, and Mexican National Health and Nutrition Survey 2006. Subjects: Mexican adults. Results: In 2010, 32 % of men and 26 % of women were normal weight. By 2050, the proportion of normal weight will decrease to 12 % and 9 % for males and females respectively, and more people will be obese than overweight. It is projected that by 2050 there will be 12 million cumulative incidence cases of diabetes and 8 million cumulative incidence cases of heart disease alone. For the thirteen diseases considered, costs of $US 806 million are estimated for 2010, projected to increase to $US 1·2 billion and $US 1·7 billion in 2030 and 2050 respectively. A 1 % reduction in BMI prevalence could save $US 43 million in health-care costs in 2030 and $US 85 million in 2050. Conclusions: Obesity rates are leading to a large health and economic burden. The projected numbers are high and Mexico should implement strong action to tackle obesity. Results presented here will be very helpful in planning and implementing policy interventions.